Pengaruh Antarmuka Pengguna (UI/UX) Terhadap Efisiensi Penggunaan Sistem Rekam Medis Elektronik oleh Tenaga Kesehatan - Datu Arya Wirawan; Deni Suhartono; Made Ari Wijaya (Journal of Computer Science and Information Technology, 2025)
The development of information technology in the health sector has encouraged the implementation of electronic medical records (EMR) systems as a solution to improve the quality of service and the efficiency of healthcare workers. However, the success of an EMR system is not only determined by its functionality, but is also greatly influenced by the design of the user interface (UI) and user experience (UX). This study aims to analyze the influence of UI/UX on the efficiency of EMR system use by healthcare workers in healthcare facilities. The research method used is a quantitative approach with a survey design. Data collection was conducted through questionnaires to 75 healthcare workers from various service units who have used the EMR system for at least six months. Data were analyzed using multiple linear regression to determine the relationship between UI/UX variables and efficiency of use. The results showed that UI/UX aspects have a positive and significant influence on the efficiency of EMR system use, with a coefficient of determination (R²) of 0.68. This indicates that 68% of the variation in efficiency of use can be explained by the quality of UI and UX. This finding emphasizes the importance of designing an intuitive, responsive, and user-friendly interface to support healthcare workers' performance. The recommendation of this research is to improve the quality of UI/UX as the main strategy in developing health information systems.